The status of female faculty in the US: Thirty-five years with equal opportunity legislation - Jane W. Loeb (Management Revue, 2006)
The status of faculty women in higher education in the U.S. is reviewed from the early 1970s, when equal employment legislation became applicable to them, to the present time. On balance, faculty women's status has improved markedly. In the past thirty five years, women have made large strides in entering academic fields that were previously predominantly male, earning doctorates, attaining full time faculty positions at all types of institutions, increasing scholarly productivity, and in narrowing the gap in salaries and ranks. While some trouble spots remain, faculty women's status is much improved.
Keywords: 650; women faculty; salary equity; academic rank; Hochschullehrer; Weibliche Arbeitskräfte; Lohndifferenzierung; Geschlecht; USA